Cisto residual de mandíbula: relato de caso e acompanhamento de 2 anos - Belizário, Aviva Raquel [UNESP] (2015)
A cyst is defined as a pathological cavity lined by epithelium and having in its interior fluid or semi-solid contents. This paper reports a case of a male patient, that went to the Surgery Clinic of Araçatuba Dental School, reporting the presence of a cyst in the jaw. On extra-oral examination, it wasn't showed any abnormalities at patient's jaw. On intra-oral examination and final reports, it wasn't identified neither signs nor symptoms related to patient's condition. Radiographically was noticed the presence of an intraosseous, radiolucent and radiopaque lesion rounding the left side of mandible. We chose to surgically remove it through enucleation technique. The suspected diagnosis of cyst was confirmed after the material taken was referred for biopsy with the definitive diagnosis of cyst Residual. The two year follow-up after surgery, showed that both the diagnostic and the treatment, obtained satisfactory results